Age estimation using aorta image analysis in the Thai population - Pornhatai Komutrattananont,; Treerat Gumpangseth,; Parison Palee,; Sukon Prasitwattanaseree,; Norzana Abd Ghafar,; Chaturong Kanchai,; Pasuk Mahakkanukrauh, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The current technology used in imaging has an increasing role in medical education. The concept of using an image analysis programme to help in estimating the age of the aorta, the largest artery, can be clearly seen to be of use, especially in establishing age changes for the identification of individuals. The purposes of the study were to investigate gross morphology, morphometric parameters, and the correlation between parameters with age of the aorta in human cadavers by using an image analysis programme. A total of 244 specimens were dissected from 4 locations of 61 human aortas from donour and autopsy cadavers with an age range of 20 to 90 years. The morphometric parameters included outer circumference, inner circumference, aortic diameter, and average thickness of all locations of the aorta. These were defined and measured by using the image analysis programme. The results of this study showed that the outer circumference (r=0.808-0.739), inner circumference (r=0.763-0.682), vertical diameter of the aorta (r=0.628-0.524) and horizontal diameter of the aorta (r=0.808-0.396) showed a significant correlation with age in all areas of the aorta. In the ascending aorta, the correlation between the outer circumference, horizontal diameter and age were higher than other variables and areas. The age equation established pertinent to the outer circumference (OC) in the ascending aorta was age = -61.648+ (1.141(OC)) with a standard error of ± 12.45 years. The age prediction equation for the horizontal diameter (HD) in the ascending aorta was age = -35.799+ (4.134(HD)) and a standard error of ± 12.43 years. In conclusion, knowledge of the structural changes associated with age can be used for age estimation in forensic anthropology.